2022
DOI: 10.1177/14614448221127899
|View full text |Cite
|
Sign up to set email alerts
|

Social media use of the police in crisis situations: A mixed-method study on communication practices of the German police

Abstract: Social media have become essential for crisis communication. While past research has focused on their role in corporate communication, studies largely ignored how public organizations use social media. Among these, the police are a particularly relevant case due to their responsibilities in society. Using a sequential mixed-methods design that combines qualitative interviews with an automated content analysis, this study analyzes how the German police use social media during community (e.g. mass shootings) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Social media has emerged as a critical platform for public organizations, including the police, to communicate during crises. Jungblut, Kümpel, and Steer (2022) utilized a sequential mixed-methods design, combining qualitative interviews with automated content analysis, to explore the communication practices of the German police on social media during crises. Their study revealed that Twitter and Facebook are primary channels for crisis communication, with the communicative styles being shaped by the platforms' unique affordances.…”
Section: Methodology Research Design: Case Studies and Content Analysismentioning
confidence: 99%
“…Social media has emerged as a critical platform for public organizations, including the police, to communicate during crises. Jungblut, Kümpel, and Steer (2022) utilized a sequential mixed-methods design, combining qualitative interviews with automated content analysis, to explore the communication practices of the German police on social media during crises. Their study revealed that Twitter and Facebook are primary channels for crisis communication, with the communicative styles being shaped by the platforms' unique affordances.…”
Section: Methodology Research Design: Case Studies and Content Analysismentioning
confidence: 99%
“…A shortcoming of digital communication research is that it primarily focuses on Twitter, a development that is often attributed to the data availability and access restriction issues shaping the computational turn of the discipline (Berry, 2011;Burgess and Bruns, 2015;Freelon, 2018;Lazer et al, 2020). However, public organizations engaged in conflict, such as the police, also primarily use Twitter and Facebook in their crisis communication (Jungblut et al, 2022). The general preference for Twitter is also prevalent in activism and war research (Seo, 2014;Bruns and Hanusch, 2017;Manor and Crilley, 2018;Özkula et al, 2022), but studies on, for instance, Instagram, YouTube and thematic forums also exist (Andén-Papadopoulos, 2014;Dinnen, 2016;Crilley and Chatterje-Doody, 2020;Al-Rawi, 2021).…”
Section: War Representations and Social Mediamentioning
confidence: 99%
“…Fiakpui (2020), recommended, in his research that Ghana police need to use social media to make a positive brand image. From the findings of Jungblut et al (2022) witnessed social media platforms are an integral part of modern policing. Also, at the organizational level of crisis communication, the messages are well constructed and therefore it has assisted in keeping reputational damages at a minimal level.…”
Section: Social Media and Corporate Reputationmentioning
confidence: 99%
“…More importantly, the police are required to create confidence and trust in society (Diphoorn & Van Stapele, 2021). In order to build trust it is necessary to encourage community participation (Jungblut et al, 2022), and also trust is closely linked to the reputation of an organization (Josang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%